Can I Get me out of my Head? Exploring Strategies for Controlling the Self-Referential Aspects of the Mind-Wandering State during Reading. Issue 6 (June 2017) - Sanders, Jet G.; Wang, Hao-Ting; Schooler, Jonathan; Smallwood, Jonathan
Trying to focus on a piece of text and keep unrelated thoughts at bay can be a surprisingly futile experience. The current study explored the effects of different instructions on participants' capacity to control their mind-wandering and maximize reading comprehension, while reading. Participants were instructed to (a) enhance focus on what was read (external) or (b) enhance meta-awareness of mind-wandering (internal). To understand when these strategies were important, we induced a state of self-focus in half of our participants at the beginning of the experiment. Results replicated the negative association between mind-wandering and comprehension and demonstrated that both internal and external instructions impacted on the efficiency of reading following a period of induced self-focus. Techniques that foster meta-awareness improved task focus but did so at the detriment of reading comprehension, while promoting a deeper engagement while reading improved comprehension with no changes in reported mind-wandering. These data provide insight into how we can control mind-wandering and improve comprehension, and they underline that a state of self-focus is a condition under which they should be employed. Furthermore, these data support component process models that propose that the self-referent mental contents that arise during mind-wandering are distinguishable from those processes that interfere with comprehension.